Brenneria spp. and Rahnella victoriana associated with acute oak decline symptoms on oak and hornbeam in Iran. Issue 4 (26th June 2019) - Moradi‐Amirabad, Yousef; Rahimian, Heshmat; Babaeizad, Valiollah; Denman, Sandra
Abstract: Decline diseases of forest trees are complex syndromes not attributable to single causal factors. In Iran, symptoms of decline disease have been observed in a number of native forest species including Quercus castaneifolia (chestnut‐leaved oak), Q. brantii (Persian oak) and Carpinus betulus (hornbeam). The symptoms are prevalent in the northern forests and the Zagros mountain forests. There are parallels between the disease in Iran and acute oak decline (AOD) reported in the UK, specifically the presence of weeping cankers, which have been attributed to a polybacterial complex wherein Brenneria goodwinii is considered a key necrogen. Based on the AOD symptomatology, and as a first step towards discovering potential causal agents of the stem weeping symptoms of affected trees in Iran, necrotic tissues were tested primarily for the presence of B. goodwinii . Symptomatic Q. castaneifolia and C. betulus from the Mazandaran Province and symptomatic Q. brantii from Kohgiluyeh and Boyerahmad Province were sampled. Isolation and culture on a selective medium yielded uniform bacterial colonies. Isolates were characterized using phenotypic and genotypic (DNA sequencing) tests. The isolates were phenotypically identical to members of Pectobacteriaceae and Yersiniaceae, specifically Brenneria and Rahnella spp. The nucleotide sequences of the 16S rRNA and housekeeping genes gyrB, infB and atpD (MLSA) amplified via PCR demonstrated that the isolates from the trees in Iran were indeed B. goodwinii, B. roseae subsp. roseae, Rahnella victoriana and an unknown species of Brenneria . Most bacteria isolated from non‐symptomatic trees were Gram‐positive, and Pseudomonas spp. were dominant, but bacterial species isolated from the diseased trees were not detected in healthy trees. Hypersensitivity response tests were positive, but inoculation on saplings was more variable with internal necrosis developing only once in the test period. Therefore, further testing is required. This is the first report of the incidence of B. goodwinii, B. roseae subsp. roseae, R. victoriana and Brenneria sp. associated with acute oak decline‐like symptoms on Q. castaneifolia, Q. brantii and C. betulus across the western forests of Iran and in the world.